Optimising Linguistic Fluency: An Empirical Inquiry Into The Integrative Efficiency Of Universal Design For Learning In Increasing English Speaking Duration. The Case Of First Year Bachelor Students In The University Of El Oued, Algeria - Cherfi, Haithem; Saadoune, Farida (University of Eloued جامعة الوادي, 2024)
This experimental study is concerned with the efficacy of Universal Design for Learning in extending English-speaking time in university, juxtaposed against the conventional classical method. The study design includes two groups, consisting of a case group exposed to Universal Design for Learning (UDL) principles and a neutral group subjected to traditional teaching methods. A quantitative analysis of the collected data is undertaken utilizing the Statistical Package for the Social Sciences (SPSS). The findings not only signify but also underscore a noteworthy escalation in the duration of English-speaking during presentations. This study contributes valuable insights into enhancing language learning experiences within university contexts, offering potential pedagogical advancements.
Article. Ex Professo. Vol 07. N.02 .University of El oued
Keywords: Universal Design for Learning; classical method; English-speaking duration; presentation